PRIORITY MANAGEMENT: REVIEW ARTICLE - Alaulddin B.Jawad; Inam Abbas Hamidi (Scholar Express Journals, 2022)
Modern technology has led to the speed and ease of information flow in front of the senior management, and accordingly. to think seriously and quickly to determine the most important things to accomplish according to the concept of identifying and classifying the works of the utmost importance among all the works entrusted to them, and they must be accomplished as quickly as possible and with the best efficiency and effectiveness to reach the primary goal with quality and at the right time .
Keywords: Priority management; accomplished; quality; information